Human Rights and Carl Schmitt’s Challenge of ‘the Political’ - Tariq Rahim (حقوق بشر)
The recognition of human dignity is the hallmark of human rights. The nature and scope of human rights is such that human persons find in them the inspiration to be truly human. A challenge to the concept of human rights rests on a skeptical understanding that these rights can be suspended. Carl Schmitt’s work provides a theoretical resource to those who seek to challenge the inviolable status of human rights. In an attempt to secure the conceptual priority of prudential reasons over moral considerations, Schmitt introduces his notion of ‘the political’ which hinges on ‘logic of exclusion’. In this paper, I highlight some points in Schmitt’s writings to show that his political philosophy stands in utter opposition to the central assumptions of human rights.